Feasibility study of fuel reactor to produce synthetic gas as an alternative energy - Tan, Kok Haw (2007)
This research is focused on the feasibility of the Fuel Reactor in order to produce synthetic gas. The Fuel Reactor uses ordinary tap water and low voltage electrical energy for producing a synthetic gas. High temperature (3000-4000°C) plasma is generated underwater by an electrical arc between carbon electrodes. The Fuel Reactor produces a mixture of carbon monoxide and hydrogen (COH 2) and this gas can burn very cleanly in oxygen or air. The objective of this research is to produce the Fuel Reactor and to test the feasibility of the Fuel Reactor to produce the synthetic gas. The idea of the project came from the rising of the fuel price and the extinction of the petroleum and the desire to find replacement for this non renewable energy. The Fuel Reactor that has been set up here was not feasible to produce the gas as expected. The main problem was the melting of the wire and the experiment has been continued for 3 times in order to test the Fuel Reactor. Future recommendation after conducting this research will be using the wire that sheathed with silicon which can withstand the heat generated by the high current flow. Another solution will be using the alternative to the copper wire that is aluminium wire which widely used in the power grid system. A sufficient ammeter should be ready in order to measure the current that draws by the Fuel Reactor. The success of this research will be a technological breakthrough in the mechanical field.